Framework For The Design And Development Of An Integrated Natural Disaster Management System In Malaysia - Amirebrahimi, Sam (2011)
The aim of this work is to develop an integrated management framework - particularly for seven of natural disasters in the country. To achieve this objective, in this work the current disaster management system of Malaysia was investigated from two points of views - individual organizations involved in the system (MICRO) and National Security council (MACRO) as the coordinative body.